2016
DOI: 10.3389/fmicb.2016.00031
|View full text |Cite
|
Sign up to set email alerts
|

Current Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus in Elderly French People: Troublesome Clones on the Horizon

Abstract: Objective: In 2015, we conducted at 44 healthcare facilities (HCFs) and 21 nursing homes (NHs) a 3-month bloodstream infection (BSI) survey, and a 1-day prevalence study to determine the rate of carriage of methicillin-resistant Staphylococcus aureus (MRSA) in 891 patients and 470 residents. We investigated the molecular characteristics of the BSI-associated and colonizing MRSA isolates, and assessed cross-transmission using double-locus sequence typing and pulsed-field gel electrophoresis protocol.Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Nonetheless, the clinical significance of qacA/B carriage itself remains unclear. While many studies report minimal qacA/B carriage in MRSA over sustained periods of time in intensive care settings, others continue to report high qacA/B carriage and reduced susceptibility to chlorhexidine in S. aureus and CoNS [91,92]. Recently, qacA/B carriage has also been reported in PVL+ve MSSA from osteomyelitis and necrotising pneumonia [92].…”
Section: ) Chlorhexidine Resistance In S Aureusmentioning
confidence: 99%
“…Nonetheless, the clinical significance of qacA/B carriage itself remains unclear. While many studies report minimal qacA/B carriage in MRSA over sustained periods of time in intensive care settings, others continue to report high qacA/B carriage and reduced susceptibility to chlorhexidine in S. aureus and CoNS [91,92]. Recently, qacA/B carriage has also been reported in PVL+ve MSSA from osteomyelitis and necrotising pneumonia [92].…”
Section: ) Chlorhexidine Resistance In S Aureusmentioning
confidence: 99%
“…The prevalence of qacA/B in S. aureus reported over the last decade is very variable although the drivers for high carriage are not clear. While some studies continue to report declining susceptibility to chlorhexidine and increasing prevalence of qacA/B in MRSA from a range of clinical settings 8,9 , other studies, including our own work, report low presence of qacA/B in S. aureus from screening samples and bacteraemia patients 10,11 . However, we have shown a high prevalence (80%) of qacA/B in S. epidermidis isolates from blood cultures randomly collected over 6 years in an intensive care unit in Scotland, with qacA/B carriage coinciding with reduced susceptibility to chlorhexidine 11 .…”
Section: Figures and Tables:mentioning
confidence: 64%
“…The host deprived of the protective role of commensal microorganisms is more vulnerable for colonization with potentially pathogenic bacteria. Rondeau et al (2016) found that the antibiotic therapy and health status of the nursing home residents were significantly associated with MRSA colonization [14]. The adverse effects of the use of antibiotics are also well-known for their contribution to the development of the acquired antibiotic resistance among microorganisms [15].…”
Section: Discussionmentioning
confidence: 99%